2005
DOI: 10.3748/wjg.v11.i11.1700
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of CD95 and soluble CD95 expression with acute rejection status of liver transplantation

Abstract: AIM:To analyze the expression levels of soluble form of CD95, CD95 ligand (sCD95 and sCD95L, respectively) in plasma and CD95 expression on CD3 + cells in livertransplanted recipients with acute rejection (AR). METHODS:Peripheral blood mononuclear cells (PBMCs) were isolated from 30 clinically liver transplanted recipients. CD95 expression on CD3 + cells was quantitatively measured by two-color fluorescence activated cell sorter (FACS) analysis. Lymphocyte surface phenotypes of CD4, CD8, CD16 and CD56 were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Therefore it would be of interest to look for parameters capable of discriminating both complications, because immunosuppression used to treat rejection further increases viral load, and it also accelerates and exacerbates recurrence of hepatitis [9]. A diversity of strategies has been implemented trying to differentiate HCV recurrence from cellular AR, such as quantification of viral HCV RNA copies in liver tissue [29], intragraft immune activation gene expression profiling [30], infiltrating leukocyte or hepatocyte apoptosis rates, as well as the expression of apoptosis related molecules CD95 and CD95L [16,19,20], but none of them became a definitive test capable of distinguishing these two entities. In fact, CD95 and CD95L intragraft protein levels have been repeatedly studied, although conclusions have been drawn that any inflammatory process increased expression of these molecules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it would be of interest to look for parameters capable of discriminating both complications, because immunosuppression used to treat rejection further increases viral load, and it also accelerates and exacerbates recurrence of hepatitis [9]. A diversity of strategies has been implemented trying to differentiate HCV recurrence from cellular AR, such as quantification of viral HCV RNA copies in liver tissue [29], intragraft immune activation gene expression profiling [30], infiltrating leukocyte or hepatocyte apoptosis rates, as well as the expression of apoptosis related molecules CD95 and CD95L [16,19,20], but none of them became a definitive test capable of distinguishing these two entities. In fact, CD95 and CD95L intragraft protein levels have been repeatedly studied, although conclusions have been drawn that any inflammatory process increased expression of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Among others tissues, CD95 is normally expressed in the liver and in most cells of the immune system, whereas CD95L shows a more restrictive tissue distribution. Remarkably, during the cellular acute rejection of the liver graft, both CD95 and CD95L are upregulated in liver tissue [14] and at least CD95 is also positively modulated in peripheral blood mononuclear cells (PBMC) [15,16]. However, the most important finding is that CD95 is also strongly overexpressed in liver tissue from HBVinfected [17] or HCV-infected patients who have not undergone transplantation [14, 18 -20], which seems to contribute to organ damage [21].…”
Section: Introductionmentioning
confidence: 99%
“…Wieland and Shipkova, Lymphocyte surface molecules 14 sCD95) in the bloodstream have been investigated to a very limited extent [76][77][78]. As suggested for sCD30, the concentration of these soluble proteins has also been considered to serve as a surrogate marker for T cell activation [79], and if true, then this would be very attractive from both analytical (commercial kits available) and pre-analytical points of view (sample stability).…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…can also be assessed as soluble form in the plasma (sCD95), and Wang and colleagues reported elevated sCD95 in liver transplant patients with acute rejection compared with stable nonrejection patients and healthy controls [78].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Other biomarkers of ACR after renal transplantation are being investigated at present using proteomic analysis of urine [6,7]. Analogous to kidney transplantation, several studies reported the identification of serum and bile biomarkers of ACR after liver transplantation [8][9][10][11][12][13][14][15]. Our group reported previously that interleukin-6 (IL-6) in bile correlated with ACR after liver transplantation in rats and deceased liver transplantation in human [16,17].…”
Section: Introductionmentioning
confidence: 98%